PENGABDIAN ORANG PERCAYA KEPADA TUHAN - Epafras Mujono; Ellya Nora Br. Manurung (JURNAL PENABIBLOS, 2024)
The writing of the results of this study is motivated by the thoughts of some believers who narrow the meaning of devotion or giving of believers to God to gifts in the form of material things only. Even though Christ redeems the believer completely, this means that the entire life of the believer belongs to Jesus, so that all parts of the believer's life can be dedicated to God. The biblical study of this article focuses on the Book of Philippians, because their devotion shows that the believers in Philippi were united together and could give their lives to fellowship with the message of the Gospel (Phil.1:3-6; 2:12) and the giving of their possessions to God, through his gift to Paul (who was in prison) who was handed over through Epaphroditus (Phil. 4:18). The 'giving of the Philippian church' based on what is written in the book of Philippians is very clear. The Philippians' giving to God is not only material but also in the form of surrendering their lives to God, namely their fellowship with the Gospel message and their obedience to God's Word. Specifically in terms of material gifts, these gifts had been given by the Philippians, not just once but many times, to Paul who was in the service of God's work.                   This research is pure library research, and is research using descriptive methods. The results of this research are a description or explanation of the devotion of believers to God with all matters related to this subject.